1971
DOI: 10.1021/bi00787a014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macrolides on peptide-bond formation and translocation

Abstract: adenosine; GMPPCP, 5'-guanylylmethylenediphosphonate; 1 optical density unit is the amount of material which in 1.0 ml would yield a value of 1.0 for the optical density measured at 260 µ in a cuvet with a path length of 1.0cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 29 publications
8
39
0
2
Order By: Relevance
“…1C) (13). This is in line with results from biochemical experiments, showing that carbomycin A inactivates peptidyl transfer in an artificial system with puromycin as the acceptor and N-acetyl-Phe-tRNA Phe as the donor (4,5). In contrast, experiments in a more realistic system with heteropolymeric mRNAs show that both fMet-Val-tRNA Val and fMet-Gly-Ile-tRNA Ile can be formed on ribosomes in complex with josamycin (7).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…1C) (13). This is in line with results from biochemical experiments, showing that carbomycin A inactivates peptidyl transfer in an artificial system with puromycin as the acceptor and N-acetyl-Phe-tRNA Phe as the donor (4,5). In contrast, experiments in a more realistic system with heteropolymeric mRNAs show that both fMet-Val-tRNA Val and fMet-Gly-Ile-tRNA Ile can be formed on ribosomes in complex with josamycin (7).…”
Section: Resultssupporting
confidence: 76%
“…It has been found that 16-membered ring macrolides such as josamycin, but not 14-membered macrolides such as erythromycin, inhibit the peptidyltransferase (PT) reaction itself (4,5). It has also been shown that both these types of macrolides cause peptidyl-tRNA dropoff from the ribosome (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work indicates that chloramphenicol and certain macrolides fail to inhibit poly(Phe) synthesis in cell extracts (25,32,34). We initially tested azithromycin and chloramphenicol in the A/T system, and a Ͻ5% decrease in poly(Phe) synthesis was detected.…”
Section: Discussionmentioning
confidence: 99%
“…An example is carbomycin A, a 16-membered macrolide that carries a large mycaminose-mycarose sugar moiety. When bound to a H. marismortui ribosome (19), this extension reaches the peptidyl-transferase center, a finding correlating well with dissociation of peptidyl-tRNAs containing 2-4 residues (19,65,75,91). In contrast, erythromycin, which binds to the macrolide pocket but does not possess a mycaminose-mycarose sugar, causes dissociation of peptidyl-tRNAs containing 6-8 residues (65).…”
Section: Troleandomycin: a Macrolide Interacts With Two Domains And Tmentioning
confidence: 99%